Framing COVID-19 and the Movement Control Order: between social responsibility and editorial ideology - Mohamed, Shafizan; Idid, Syed Arabi (2021)
Pandemics pose serious global threats. The consequences of a large-scale health crisis can be disastrous if they are not carefully contained. In times like these, the media plays an important role in educating the public and maintaining social order by covering both insightful and positive news. Using a framing theory perspective, this study examines media coverage of the COVID-19 health crisis in Malaysia during the country's Minimal Control Order (MCO) period. According to the findings of a content analysis of The Star Online (N=870) and Malaysiakini Bahasa (N=870), technical implementation of the Movement Control Order (MCO) and the economy dominated the news. Despite the similarities in the topics covered, the study discovered that when it came to framing the news, the government-friendly The Star was more optimistic about how the crisis is progressing than the more liberal Malaysiakini, implying that even during a pandemic, local newspapers couldn't stray too far from their political and ideological positions.